Characteristics of Patient with Benign Paroxysmal Positional Vertigo in Dr. Hasan Sadikin General Hospital Bandung from 2009‒2013 - Intan Datya Kirana; Yussy Afriani Dewi; Titing Nurhayati (Althea Medical Journal, 2016)
Background: Benign Paroxysmal Positional Vertigo (BPPV) is a vestibular disorder marked by episodes of vertigo and triggered by a change in the head position. It is characterized by short yet severe episodes of vertigo and possibly accompanied by nausea and vomiting. The BPPV is usually idiopathic and foundamong people aged 46‒50 years old. There are pharmacological and non pharmacological treatment used for BPPV. Non-pharmacological treatment includes Epley, Semont, Lempert, Forced Prolonged Position, andBrandt-Daroff maneuvers and pharmacological onebenzodiazepine and antihistamines. This study aimed to examine the characteristics of patient with BPPV based on their complaint and prescribed treatment.Methods: This was a descriptive-retrospective study conducted on April–June 2014 using secondary data from medical records of patient with BPPV in Dr. Hasan Sadikin General Hospital Bandung from 2009‒2013. The variables include gender, age, occupation, accompanying disease, complaints, supporting examinations, and treatment.Results: There were 74 subjects; 66.22% were female and 33.78% were male. Most of patients with BPPV aged around 41‒50 years old (39.19%). Furthermore, 93.24% had a major complaint of headache and spinning sensation, and >60% nausea and vomiting. The most prescribed therapy was Betahistine (86.49%). Meanwhile, a maneuver of non-pharmacological treatment was rarely done (8.11%).Conclusions: The BPPV occurs more in older women. The major complaint is headache and spinning sensation affected by the head position and accompanied by nausea and vomiting. Lastly, non-pharmacological treatment is rarely performed in handling patient with BPPV. [AMJ.2016;3(2):275–9]DOI: 10.15850/amj.v3n2.800